A User Study on the Feasibility and Acceptance of Delivering Physical Activity Programs to Older Adults through Conversational Agents. (December 2020) - Chin, Jessie; Quinn, Kelly; Muramatsu, Naoko; Marquez, David
The implementation of evidence-based physical activity (PA) programs for older adults is limited in part due to the administration-related personnel costs. The rapid growth of the off-the-shelf smart speakers, conversational agents (CAs), demonstrates the potential of scalable delivery of PA programs to older adults at home. We implemented a PA virtual coach based on an evidence-based PA program on a Google Home device, and conducted a user study to examine how older adults interact with the virtual coach. Results suggested that all older adults were able to complete the PA program with guidance from the virtual coach, and showed high acceptance and intentions to use CAs in the future. Analyses on conversation turn-taking further suggested that all older adults (including 80% novice CAs users) experienced minimum difficulty talking with the PA virtual coach. Relationships among age, technology acceptance, conversation patterns and the perceived sociability of CAs are also discussed.